2023
DOI: 10.1055/a-2057-0205
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia, More Than Just Muscle Atrophy: Imaging Methods for the Assessment of Muscle Quantity and Quality

Abstract: Background Sarcopenia, a progressive reduction of muscle mass and function, is associated with adverse outcomes in the elderly. Sarcopenia and muscle atrophy are not equal processes. Low muscle strength in association with muscle quantity/quality reduction is currently the optimal method for assessing sarcopenia. There is a practical need for indirect measurement of muscle strength using state-of-the-art imaging techniques. Methods The following provides a narrative, broad review of all current ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Exact or functional muscle mass in these patients might be overestimated due to myosteatosis, which should be considered in the assessment of sarcopenia in patients with CD. Myosteatosis, a term comprising intermuscular, intramuscular, and/or intramyocellular fat, negatively correlates with muscle strength, quality, or function [13]. Muscle strength and quality are better than mass in predicting the presence of sarcopenia and adverse outcomes [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exact or functional muscle mass in these patients might be overestimated due to myosteatosis, which should be considered in the assessment of sarcopenia in patients with CD. Myosteatosis, a term comprising intermuscular, intramuscular, and/or intramyocellular fat, negatively correlates with muscle strength, quality, or function [13]. Muscle strength and quality are better than mass in predicting the presence of sarcopenia and adverse outcomes [8].…”
Section: Discussionmentioning
confidence: 99%
“…bidity/mortality and an independent risk factor for many diseases [13]. Sarcopenia may regress with proper treatment and close follow-up [9].…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reliability can be controlled through adequate training. Another limitation of ultrasonography is that the measurement sites are not unified for the assessment 33 …”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that radiation exposure is negligible and ideas for ultrasound alternatives are being developed. 9 However, with adjusted hazard ratios of about 1.3 per change in category of low-attenuation "skeletal muscle index", the question is if the resources spent in order to pare down the at-risk population by a few percent are larger than those that could be saved.…”
mentioning
confidence: 99%